On the Simulation of Lightning and Flash Flood Producing Thunderstorms in the Northeastern Bangladesh (Journal of Engineering Science, 2020)
This study is an attempt to simulate the tropospheric conditions associated with lightning and thunderstorms, which occurred during 28-30 March 2017 over northeastern Bangladesh using WRF model. At Sylhet, rainfall amounts of 119 mm and 134 mm are found to occur on 29 March and 31 March 2017 respectively. The continuous very heavy rainfall has been responsible for the devastating flash flood in Sunamganj and adjoining areas in 2017. The study shows that forecasting of lightning and flash flood producing thunderstorms is possible by analyzing different meteorological parameters simulated by WRF Model. The simulated parameters are rainfall, sea level pressure, geopotential height (m), Convective Available Potential Energy (CAPE), winds at various tropospheric levels, cloud water mixing ratio and ice water mixing ratio, vorticity and x, y, z wind components. A low pressure area and strong circulations are found to develop over West Bengal and adjoining Bangladesh with extended troughs towards northeast, having strong flows of southwesterly to southsoutheasterly winds distinctly visible at low level over the Bay of Bengal and Bangladesh. Interaction of northwesterly flows of winds at 500 hPa level and southerly flow coming from the Bay of Bengal is found to produce sufficient instability in the troposphere to develop severe thunderstorms which when moved over northeast Bangladesh/Meghalaya have become stronger due to orographic influence, thereby become lightning and flash flood producing thunderstorms. The thunderstorms become more marked due to the presence of westerly jet stream of 40 ms-1 over Bangladesh and India. The persisting characteristics of the circulation over West Bengal and Bangladesh, the micro-circulation, the intense geopotential low at 850 hPa and their eastward extension have been responsible for continuous heavy to very heavy rainfall over Sylhet and Meghalayan region, causing wide-spread intense flash floods over there. On 29 March 2017, cloud water mixing ratio is found to range from 160 to 1100 mgm-3 and ice water mixing ratio from 27 to 100 mgm-3 at different locations. The maximum cloud water mixing ratio values are 1100 and 1000 mgm-3 at Cherrapunji and Sylhet respectively, where torrential rain has occurred. The high values of cloud water mixing ratio and ice water mixing ratio in the upper troposphere over northeastern Bangladesh and adjoining areas indicates significant convection in the troposphere and have been responsible for moderate to severe lightning. The distribution of CAPE has also shown increasing higher values, indicating moderate to severe lightning.Journal of Engineering Science 11(1), 2020, 133-146